Fission technique on sea cucumbers (Holothuroidea): An alternative method for seed production - Muzahar Muzahar; Wulandari Rika; Putri Dwi Septiani; Yulianto Tri; Irawan Henky; Bakkara Okto Rimandi (BIO Web of Conferences)
This study aimed to determine the successive level of fission technique on several sea cucumbers (Holothuroidea) in littoral zone of Madong Bay, Tanjungpinang. The fission technique was performed by tying the middle part of the sea cucumber’s body using a rubber band. Parameters observed were composed of: (a) the occurrence of autotomy on pre- and post-treatment period, (b) successive rate of fission technique (%), (c) fission duration, (d) survival rate on post-treatment period. All data were analyzed descriptively. The results showed that: (1) Only gold sea cucumber Stichopus chloronotus that could perform autotomy on post- treatment period, (2) The successive rate of fission technique on Stichopus chloronotus and Holothuria atra was 83.33% and 33.33%, respectively, while fission was absent on Holothuria scabra and Holothuria sp. (0%), (3) The fastest fission process was found on Stichopus chloronotus at 1.2 hours, after applying the fission technique at 24±2 hours and Holothuria atra was at 24-48 hours, (4) The survival rate on post-treatment period was 66.67% in Stichopus chloronotus and 41.67% in Holothuria atra, while Holothuria scabra was 66.67% and Holothuria sp. was 11.11%. Fission technique is more suitable for Stichopus chloronotus as an alternative method for seed supply in grow-out culture activities.